A novel fluorescence "on–off–on" chemosensor for Hg2+via a water-assistant blocking heavy atom effect. Issue 38 (23rd August 2016) - Wu, Chong; Zhao, Jiang-Lin; Jiang, Xue-Kai; Wang, Chuan-Zeng; Ni, Xin-Long; Zeng, Xi; Redshaw, Carl; Yamato, Takehiko
Abstract : The heavy atom effect and blocking thereof were demonstrated within the same system by the use of a C 3 -symmetric homooxacalix[3]arene scaffold. Abstract : Upper rim pyrene-functionalized hexahomotrioxacalix[3]areneL was synthesized via Click chemistry, and its fluorescence behaviors toward several common metal cations were investigated.L exhibited a significant fluorescence quenching response to Hg 2+ in CH3 CN solution, which was unaffected by the coexistence of other competitive metal cations. Thus, L can be utilized as a highly selective and sensitive fluorescent chemosensor for Hg 2+ with a detection limit in the nM level. Interestingly, the quenched fluorescence emission can be successfully revived upon the addition of water. In this process, the heavy atom effect of Hg 2+ can be blocked by further coordination of a water molecule and resulted in the revival of the fluorescence emission ofL /Hg 2+ complex. Particularly, other polar solvents such as CH3 OH and CH3 CH2 OH also have the ability to revive the fluorescence emission of theL /Hg 2+ complex, but on a much smaller scale than observed for H2 O. The heavy atom effect and blocking thereof were demonstrated within the same system by the use of a C 3 -symmetric homooxacalix[3]arene scaffold. The present studies provided further evidence for the blocking heavy atom effect.